2019
DOI: 10.1287/isre.2018.0818
|View full text |Cite
|
Sign up to set email alerts
|

Relative Privacy Valuations Under Varying Disclosure Characteristics

Abstract: We investigate changes to the value individuals place on the online disclosure of their private information in the presence of multiple privacy factors. We use an incentive compatible mechanism to capture individuals' willingness-to-accept (WTA) for a privacy disclosure in a series of three randomized experiments. Each experiment manipulates characteristics of a required privacy disclosure by altering the information context, intended secondary use of the disclosed private information, and the requirement to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To put estimates in context, we compare our baseline data valuations to a number of others in the literature in Section 3, and we compare the results across the YouGov and DDP samples. We also field an additional study to demonstrate the stated use of the respondents' data doesn't impact initial and revised valuations, consistent with Buckman et al (2019).…”
Section: Experimental Designmentioning
confidence: 65%
See 1 more Smart Citation
“…To put estimates in context, we compare our baseline data valuations to a number of others in the literature in Section 3, and we compare the results across the YouGov and DDP samples. We also field an additional study to demonstrate the stated use of the respondents' data doesn't impact initial and revised valuations, consistent with Buckman et al (2019).…”
Section: Experimental Designmentioning
confidence: 65%
“…To ensure that our results are not sensitive to this particular stated data use, we carry out an additional robustness exercise. Buckman et al (2019) finds a null result comparing differences in valuations for personal data when the data is shared with third parties or not. To confirm this finding in our setting, we conduct a follow-up study (N=500, recruited on Amazon MTurk) where we manipulate information presented to respondents on whether we will use their Facebook data for research purposes or commercial purposes.…”
Section: Baseline Resultsmentioning
confidence: 99%
“…Therefore, previous studies focus on the value of user privacy information [13], motivation of disclosure [7,38], privacy disclosure, and competition in the two-sided market of the platform [35]. By contrast, we further reveal the impact of consumer data privacy disclosure level on the matching level of the platform, the consumer, and the merchants.…”
Section: Platform Business Model and Data Strategymentioning
confidence: 84%
“…Most papers admit that the use of consumer private information data by the platform will have negative effects on consumers [12]. Online consumers' privacy disclosure on the platform helps the personalized recommendation system and positively affects consumers' willingness to pay [38]. However, too much information disclosed by consumers will be used to conduct business development, such as enhancing the targeted ability of advertising recommendation systems, which obviously hurts consumers to some extent.…”
Section: Platform Business Model and Data Strategymentioning
confidence: 99%
“…Personal information is considered to be a resource or a social commodity (Buckman et al, 2019; Cloarec et al, 2022; Jiang et al, 2013) insofar as it enables firms not only to provide accurate product recommendations and customized content to personalize the consumer's online experience but also to create streams of revenue by selling consumer data to information brokers (Buckman et al, 2019). Studies have shown that consumers demand monetary value in exchange for providing their personal information to firms (Buckman et al, 2019; Tomaino et al, 2022). Hence, concerning social exchange, disclosing personal information to e‐retailers to obtain services can be considered a form of resource exchange (White, 2004).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%